The blue carbuncle - Doyle, Conan Arthur; Alex Woolf (London: Arcturus, 2022)
Join world-famous detective Sherlock Holmes and his ever-loyal sidekick Dr. Watson as they embark on a daring adventure. When the Countess of Morcar's priceless blue jewel is stolen, a former thief is charged with the crime, but is he really guilty? Never fear: Sherlock Holmes is on the case, and the truth will out! This thrilling tale has been retold and adapted with new illustrations, making it perfect for younger readers